Islamic finance in Hong Kong - Zul Kepli, Mohd Yazid (Hong Kong Law Journal, 2012)
Rapid development and commercialisation within the emerging fi eld of Islamic finance provide strong evidence of its sustainability. The Islamic finance industry has experienced remarkable growth, expanding into a market worth more than US$1 trillion. This consistent growth, along with the industry’s proven ability to safely navigate a global recession and fi nancial crisis while still designing innovative products, indicates its resilience and competitive edge. Hong Kong brought Islamic fi nance into its fi nance portfolio after the former Chief Executive highlighted the desire to acquire a bigger slice of the market in 2007. However, many investors, practitioners and academicians still lack a clear understanding of this new type of fi nancing. This article explains Islamic finance and its current position in Hong Kong, together with the legal and regulatory challenges it faces. It also covers the Hong Kong Government’s March 2012 consultation on proposed amendments to tax legislation to promote the development of a local Islamic bond (sukuk) market.